2017
DOI: 10.1016/j.aogh.2016.04.672
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of Indian HIV Clinicians Toward Depression in People Living with HIV

Abstract: BACKGROUND Depression in people living with HIV (PLHIV) is highly prevalent and associated with increased morbidity and mortality. In India, where access to mental health specialists is limited, little is known about the attitude of HIV clinicians towards depression in PLHIV. METHODS We administered a questionnaire to HIV clinicians attending the 2015 Chennai Anti Retroviral Therapy symposium that assessed respondents’ level of agreement with 29 statements regarding the etiology, importance, and management o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…Three studies examined the role of HIV-stigma in NCD diagnosis and treatment, and all focused on identifying and managing depression [ 45 , 49 , 50 ]. One small qualitative study examined the adaptation of an effective depression screening tool for low-income African Americans living with HIV.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Three studies examined the role of HIV-stigma in NCD diagnosis and treatment, and all focused on identifying and managing depression [ 45 , 49 , 50 ]. One small qualitative study examined the adaptation of an effective depression screening tool for low-income African Americans living with HIV.…”
Section: Resultsmentioning
confidence: 99%
“…While this study included only seven providers and staff with training in medicine and social work, it found that HIV stigma interferes with clinical efforts to identify individuals struggling with depression [ 49 ]. In a cross-sectional study in India with health providers, when asked about their attitudes towards PLHIV with depression, 62% of respondents were either neutral or agreed with the statement “depression is a sign of personal weakness,” and 53% of respondents felt that it was difficult to work with depressed PLHIV [ 50 ]. A cross-sectional study on barriers to mental health treatment among veterans living with HIV in the United States found that among those with positive Patient Health Questionnaire-2 screens, participants who reported experiencing HIV stigma were more likely to be in treatment (χ2 = 4.22, P = .04) compared to those who did not report HIV stigma.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations